Imaging features associated with the susceptibility to brain fog: a major secondary complication observed in patients with ischemic stroke - Paulinus et al. (Rwanda Medical Journal)
INTRODUCTION: Stroke is associated with an increased risk of brain fog with a variable impact on cognition. While some stroke survivors show a decline in cognitive functions, others have stable cognitions or revert to baseline cognitive functioning. Understanding the phenomenon of brain fog following stroke is necessary for prompt intervention and management as it is unclear whether Computed Tomography (CT) or Magnetic Resonance Imaging (MRI) features of the brain in patients with ischemic stroke are associated with future risk of secondary complications, hence, the rationale for the study. The purpose was to assess the imaging features associated with susceptibility to brain fog.